ABU HASAN KRUENG KALEE: THE CHARISMATIC ULAMA OF ACEH - Safrina Safrina; Aslam Nur; Fauziah Nurdin (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
Abu Hasan Krueng Kalee is one of Aceh's charismatic scholars who teaches religious knowledge and other sciences. Abu Hasan Krueng Kalee has an important role in the sustainability of education, politics, and religion in Aceh. The research location that the author examined was Siem Village, Darussalam Sub-District. In this study, the authors used historical research methods, namely investigations that apply scientific solutions to the historical perspective of a problem with the steps of data collection, source criticism, interpretation, and writing method. The author draws a number of conclusions concerning Teungku Hasan bin Teungku Muhammad Hanafiyyah bin Teungku Shaykh 'Abbas bin Teungku Muhammad Fadhil based on the findings of the investigation. Muhammad Hasan was given the first name when he was born on 13 Rajab 1303 H, which corresponds to 18 April 1886 AD, in Gampong Langgoe Meunasah Keutumbu Village, Sangeue, Pidie. Teungku Haji Muhammad Hanafiyah bin Teungku Sheikh Abbas, often known as Teungku Chik Krueng Kalee One or Teungku Haji Muda Krueng Kalee, is the father of Abu Hasan Krueng Kalee. Nya'Ti Hafsah bint Teungku Ismail, the mother of Abu Hasan Krueng Kalee, was of Arab ancestry and migrated through Pase. Teungku Syekh Abdul Wahab and Asiah, two brothers of Abu Hasan Krueng Kalee.. Abu Hasan Krueng Kalee's contributions to religion and the country have been made in the areas of politics, education, and religion. Additionally, works of Abu Hasan Krueng Kalee might be used to instruct students. The writings include “Risalah Latifah Fi Adabi’z_Zikry” as well as “Jawahiru’I-‘ulum Fi kasyfi’I-ma’lum, An’amatu’I-fa-idatu fi isti’mali qa’odati’r-rabitat, Siraju’s-Salikin’ala minhaju’I-‘abidin.